Penentuan Premi Tunggal Asuransi Jiwa Dwiguna Unit Link dengan Garansi Minimum Menggunakan Metode Annual Ratchet dan Model Black Scholes - SHELLA RIZKY AMALIA; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2021)
Unit-linked Endowment life insurance is a Endowment life insurance that combines the benefits of insurance and investment. In determining the unit-linked Endowment life insurance premium, it is necessary to have a minimum guarantee value to overcome the risk of loss for the policyholder. The method that can be used is the Annual Ratchet method and the Black Scholes Model. The data used in this study is the daily closing stock data of PT. Astra Internasional and Bank Indonesia interest rates in January 2020. Life probability data is based on the 2019 Mortality Table. The results obtained in this study are single premium net Endowment unit-linked life insurance using the Annual Ratchet method and the Black Scholes model. Based on the case study, it is concluded that the premium for unit-linked dual-purpose life insurance with the Black-Scholes model is greater than the premium for the annual ratchet method.